ANALISIS KINERJA INDUSTRI PERBANKAN SYARIAH DENGAN PENGUKURAN TOTAL ASET PADA BANK SYARIAH YANG MENGUNGKAPKAN DANA ZAKAT DAN KEBAIKAN - Alfathin, Akmal; Fitrijanti, Tettet (Review of Accounting and Business, 2020)
This research was conduct to examine the effect of compilation party funds (DPK), Financing to Deposit Ratio (FDR), zakat funds and benevolence funds on total assets of Islamic banking and to see the contribution of the Islamic banking industry to the national banking industry by employing the random effect model method and analysis of secondary data processing. This research uses a five-year (2014-2018) of Islamic banking. The result of random effect model shows that influence simultaneously variable to Total asset Islamic banking. The secondary data processing show contribution From Islamic banking industry to the national banking industry of 4%.